Tissue Engineering of the Penis - Manish N. Patel; Anthony Atala (The Scientific World Journal)
Congenital disorders, cancer, trauma, or other conditions of the genitourinary tract can lead to significant organ damage or loss of function, necessitating eventual reconstruction or replacement of the damaged structures. However, current reconstructive techniques are limited by issues of tissue availability and compatibility. Physicians and scientists have begun to explore tissue engineering and regenerative medicine strategies for repair and reconstruction of the genitourinary tract. Tissue engineering allows the development of biological substitutes which could potentially restore normal function. Tissue engineering efforts designed to treat or replace most organs are currently being undertaken. Most of these efforts have occurred within the past decade. However, before these engineering techniques can be applied to humans, further studies are needed to ensure the safety and efficacy of these new materials. Recent progress suggests that engineered urologic tissues and cell therapy may soon have clinical applicability.